Carotenoid and color changes in traditionally flaked and extruded products - Cueto, Mario Alberto (2017)
The objective of this study was to evaluate the impact of process and formulation on individual carotenoid loss in traditionally prepared cornflakes and those prepared by extrusion. The first step in the traditional process (maize grits cooking) promoted a 60% lutein content reduction and 40% in zeaxanthin loss, showing lutein more susceptibility to isomerization and decomposition. After toasting, the last step, the total loss averaged 80% for both compounds. The extruded maize in a plain formulation showed a 35% lutein and zeaxanthin reduction. However, in samples containing quinoa the decrease reached 60%, and the major loss (80%) was found in chia-containing formulations. Correlations between the color coordinate b⁄, total and individual carotenoid content, were obtained. It is of a major importance that the efforts to increase carotenoid content in raw materials are complemented with attempts to reduce the losses during processing.